Growth oriented macroeconomic policies for small islands economies: Lessons from Singapore - Anis Chowdhury (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Most small island economies or microstates have distinctly different characteristics from larger developing economies. They are more open and vulnerable to external and environmental shocks, resulting in high output volatility. Most of them also suffer from locational disadvantages. Although a few small island economies have succeeded in generating sustained rapid growth and reducing poverty, most have dismal growth performance, resulting in high unemployment and poverty. Although macroeconomic policies play an important role in growth and poverty reduction, there has been very little work on the issue for small island economies or microstates. Most work follows the conventional framework and finds no or very little effectiveness of macroeconomic.
Keywords: E5; E6; N1; O1; 330; Caribbean; Pacific Islands; fiscal policy; small open economies; Wirtschaftspolitik; Policy-Mix; Wirtschaftswachstum; Kleines-Land-Modell; Insel; Karibische Staaten; Pazifischer Ozean